Biomolecules‐Incorporated Metal‐Organic Frameworks Gated Light‐Sensitive Organic Photoelectrochemical Transistor for Biodetection - Li, Cheng‐Jie; Hu, Jin; Gao, Ge; Chen, Jia‐Hao; Wang, Cheng‐Shuang; Zhou, Hong; Chen, Guangxu; Qu, Peng; Lin, Peng; Zhao, Wei‐Wei (Advanced functional materials, 2023)
Incorporating biomolecules into metal‐organic frameworks (MOFs) as exoskeletons to form biomolecules‐MOFs biohybrids has attracted great attention as an emerging class of advanced materials. Organic devices have been shown as powerful platforms for next‐generation bioelectronics, such as wearable biosensors, tissue engineering constructs, and neural interfaces. Herein, biomolecules‐incorporated MOFs as innovative gating module is realized for the first time, which is exemplified by biocatalytic precipitation (BCP)‐oriented horseradish peroxidase (HRP)‐embedded zeolitic imidazolate framework‐90 (HRP@ZIF‐90)/CdIn2S4 gated organic photoelectrochemical transistor under light illumination. In connection to a sandwich immunocomplexing targeting the model analyte human IgG, the IgG‐dependent generation of H2O2 and the tandem HRP‐triggered BCP reaction can cause the in situ blocking of the pore network of ZIF‐90, leading to variant gating effect with corresponding responses of the device. This representative biodetection achieved good analytical performance with a wide linear range and a low detection limit of 100 fg mL−1. In the view of the plentiful biomolecule‐MOF complexes and their potential interactions with organic systems, this study provides a proof‐of‐concept study for the generic development of biomolecules‐MOFs‐gated electronics and beyond. Herein, biomolecules‐incorporated MOFs as innovative gating module is realized for the first time, which is exemplified by biocatalytic precipitation‐oriented horseradish peroxidase (HRP)‐embedded zeolitic imidazolate framework‐90 (HRP@ZIF‐90)/CdIn2S4 gated organic photoelectrochemical transistor under light illumination. By linking with a sandwich immunoassay, the proposed biosensor achieved good analytical performance at zero gate bias.